An RNA interference phenotypic screen identifies a role for FGF signals in colon cancer progression - Leushacke, Marc; Spörle, Ralf; Bernemann, Christof; Brouwer-Lehmitz, Antje; Fritzmann, Johannes; Theis, Mirko; Buchholz, Frank; Herrmann, Bernhard G.; Morkel, Markus (PLOS ONE, 2011)
In tumor cells, stepwise oncogenic deregulation of signaling cascades induces alterations of cellular morphology and promotes the acquisition of malignant traits. Here, we identified a set of 21 genes, including FGF9, as determinants of tumor cell morphology by an RNA interference phenotypic screen in SW480 colon cancer cells. Using a panel of small molecular inhibitors, we subsequently established phenotypic effects, downstream signaling cascades, and associated gene expression signatures of FGF receptor signals. We found that inhibition of FGF signals induces epithelial cell adhesion and loss of motility in colon cancer cells. These effects are mediated via the mitogen-activated protein kinase (MAPK) and Rho GTPase cascades. In agreement with these findings, inhibition of the MEK1/2 or JNK cascades, but not of the PI3K-AKT signaling axis also induced epithelial cell morphology. Finally, we found that expression of FGF9 was strong in a subset of advanced colon cancers, and overexpression negatively correlated with patients' survival. Our functional and expression analyses suggest that FGF receptor signals can contribute to colon cancer progression.